Administration of an Amino Acid–Based Regimen for the Management of Autonomic Nervous System Dysfunction Related to Combat-Induced Illness. (January 2014) - Shell, William E; Charuvastra, Marcus; Breitstein, Mira; Pavlik, Stephanie L.; Charuvastra, Anthony; May, Lawrence; Silver, David S.
The etiology and pathophysiology of posttraumatic stress disorder (PTSD) remains poorly understood. The nutritional deficiencies associated with the altered metabolic processes of PTSD have not previously been studied in detail. This pilot study measured the reduction in symptoms in 21 military veterans reporting moderate to severe symptoms associated with PTSD. Two amino acid-based medical foods specifically formulated with biogenic amines and other nutrients were administered to study subjects targeting specific neurotransmitter deficiencies resulting from altered metabolic activity associated with PTSD. This study included the Physician Checklist – Military (PCL-M), Short Form General Health Survey (SF-36), and Epworth Sleepiness Scale to measure the change in each subject's score after 30 days of administration. An average decrease of 17 points was seen in the PCL-M, indicating a reduction in PTSD symptoms ( P < 0.001). The mental health component of the SF-36 showed an average 57% increase in the subjects' mental health rating ( P < 0.001). The results of this initial study demonstrate that addressing the increased dietary requirements of PTSD can improve symptoms of the disease while eliminating significant side effects. A larger, double-blind, randomized, placebo-controlled trial is warranted.